THE WORK CATEGORY IN THE INTEGRATED TRANSPORT SYSTEM OF FORTALEZA (ITS-FOR) - Porto Neto, Edilson da Silva; Santana, Gabriel Augusto Coelho de (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1042, 2021)
In this article, we intend to discuss the sociospatial relations established within the scope of the Integrated Transport System of Fortaleza (SIT-FOR). In order to do this, we use the category of work, understanding in a Marxist perspective that it is based on labor relations that women and men mediate their relationship with other elements of nature and constitute themselves as social beings. In this sense, in unveiling the roles that the transport system plays in cities, as in ensuring the mobility of the working class towards workplaces, we cannot fail to realize that also the class contradictions engendered in the conflict between bus drivers, collectors and businessmen in the sector are part of the process of (re) producing urban space in cities like Fortaleza.